A SURVEY OF ANT COLONY BASED ROUTING ALGORITHMS FOR MANET - Sutariya, Dharmendra; Kamboj, Pariza (European Scientific Journal, ESJ, 2014)
A Mobile ad hoc network (MANET) is a collection of wireless mobile nodes which dynamically join the network and cooperate with each other for multi-hop communication in absence of infrastructure or centralized administration. Routing in MANET is specially challenging due to the variation of network characteristic like traffic load and topology may vary in stochastic and time varying manner. Swarm Intelligence (SI) based techniques such as Ant Colony Optimization (ACO) algorithms have shown to be a good technique for developing routing algorithms for ad hoc networks. Ant based routing algorithms are based on the foraging behaviour of ants. In recent years several ant colony optimization based algorithms were introduced to solve multi constraint QoS routing problems of ad hoc network. They are more robust, reliable and scalable compared to the conventional routing algorithms available in ad hoc network. In this paper, survey of various ant based routing algorithms is done and have been summarize with various attributes to provide a status of research work done in this field.